2020
DOI: 10.14202/vetworld.2020.1549-1554
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anthelmintic activity of aqueous and ethanol extracts of Paraserianthes falcataria bark waste against Haemonchus contortus obtained from a local slaughterhouse in Indonesia

Abstract: Aim: This study was conducted to determine the anthelmintic activity of aqueous and ethanol extracts of Paraserianthes falcataria bark against Haemonchus contortus. Materials and Methods: Ethanol extract of bark (E.E.B.) waste and aqueous extract of bark (A.E.B.) waste of P. falcataria (at concentrations 0, 0.2, 0.4, 0.8, 1, 2.5, and 5%) and albendazole (2 mg/ml) as the positive control were placed in separate Petri dishes (50 mm). Twenty H. contortus worms were placed in Petri dishes and incubated at 37°C fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…One effort to deal with anthelmintic resistance is the use of natural anthelmintics [6]. The bark of Paraserianthes falcataria has been confirmed to have active compounds that succeed in killing H. contortus in vitro, and when observed using SEM, it shows that there is damage to the cuticle structure [7]; the same results have also been found in the fruit peel of Carica pubescens.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…One effort to deal with anthelmintic resistance is the use of natural anthelmintics [6]. The bark of Paraserianthes falcataria has been confirmed to have active compounds that succeed in killing H. contortus in vitro, and when observed using SEM, it shows that there is damage to the cuticle structure [7]; the same results have also been found in the fruit peel of Carica pubescens.…”
Section: Introductionmentioning
confidence: 77%
“…Blood sampling was carried out on day 0 and on day 28. Blood tests include Hb levels, erythrocyte count, PCV, leukocyte count and leukocyte differential, and blood chemistry with Frye et al [17]. 2.4.4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The damage to the anterior end and cuticle that experienced abrasion proved that IAE interacted with the nematode cuticle. Baihaqi et al [19] stated that an in vitro extract of P. falcataria's bark waste caused damage to the buccal area, and aggregate built up in the cuticle annular. Acevado-Ramírez et al [27] stated that Castanea sativa caused damage around the mouth, anus, vulva, copular bursa, and cuticle of worms.…”
Section: Discussionmentioning
confidence: 99%
“…Mishra et al[18] also found that tannins and saponins are present in I. tinctoria. Tannins, saponins, flavonoids, and alkaloids in the extract of P. falcaria have previously been shown to have an anthelmintic effect against H. contortus[19].Klongsiriwet et al…”
mentioning
confidence: 99%